HUBUNGAN ANTARA BEBAN KERJA DAN IKLIM KERJA DENGAN KELELAHAN KERJA PADA PEKERJAAN PENGUKURAN TANAH MENGGUNAKAN ALAT TEODOLIT - Oceania Starizky; Ekawati Ekawati; Siswi Jayanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Fatigue is a mechanism of body protection to avoid further body damage. Fatigue increase fault in working and the most fatal effects is an accident. Work load and work climate are some of factors that cause fatigue. The purpose of this study was to analyze the correlation between work load and work climate with fatigue in land surveying job using theodolite. This study used an explanatory research with cross sectional approach. Population of this study were 208 students of civil engineering in 2nd semester school term 2015/2016 and 36 students who using theodolite were choosen to be respondents. The instrument used in this study including stopwatch to measure work load, Questemp 34 to measure work climate, and Deary-Liewald Time Task application to measure fatigue. The results of this study show 52,8% respondent with light workload, 66,7% respondent working in substandard work climate, and 91,7 % respondent with light fatigue. The result of statistic test using Rank Spearmen Correlation Test, there were a significant correlation between workload and fatigue (p=0,01) and there’s no correlation between work climate and fatigue (p=0,706). To decrease workload and fatigue when practice, students were advised to set tripod fit to their body and wear hat to avoid heat exposure from the sun.